Spinal Intramedullary Abscess Secondary to Dermal Sinus in Children - Prasad, G. Lakshmi; Hegde, Ajay; Divya, S. (European Journal of Pediatric Surgery, 2019)
Introduction Congenital dermal sinuses (CDS) are uncommon lesions. They are most often noted in lumbosacral region and may lead to meningitis or spinal abscess. Intramedullary spinal cord abscess (IMSCA) due to CDS is rare and often co-exists with an inclusion tumor such as dermoid/epidermoid cyst.Materials and Methods Literature review was done to analyze all cases of pediatric IMSCA secondary to CDS by searching online databases starting from the oldest case reported.Results Only 50 cases have been reported and were analyzed. Mean age was 22.6 months (range 1 month–15 years). Fever, acute flaccid lower limb weakness, and urinary disturbances were the most common presenting features. Dermal sinus was commonest in lumbosacral region. Inclusion cysts were observed in 50% of cases. Staphylococcus aureus was the most the common organism. Mean follow-up duration was 18.2 months (range 1 week–156 months). Majority of the cases underwent multilevel laminectomy with myelotomy and drainage of abscess. Outcome was good-to-excellent in around 60% cases with four deaths. Presence of fever and limb weakness was significantly associated with poor outcomes.Conclusion Intramedullary abscess secondary to CDS is very rare. Complete sinus tract excision, myelotomy and drainage of abscess, and decompression of co-existent inclusion cysts with prolonged antibiotic therapy remain the standard treatment. Approximately 60% cases achieve good outcomes. Fever and limb weakness portend poorer outcomes than those without.
Keywords: spinal abscess; intramedullary abscess; pediatric; dermal sinus; review